Personality Traits, Consumer Animosity, and Foreign Product Avoidance: The Moderating Role of Individual Cultural Characteristics - Tokar, Sergii; Leonidou, Leonidas C.; Christodoulides, Paul; Kvasova, Olga (My University, 2019)
Although personality and cultural traits were found to be important predictors or moderators of consumer attitudes and behavior, their relationship to consumer animosity has not yet been studied. This article reports the findings of a study conducted with 606 Ukrainian consumers, which aims to identify personality drivers and behavioral outcomes of consumer animosity as well as the moderating role of cultural characteristics. Structural equation modeling reveals that extraversion and conscientiousness have a negative effect on consumer animosity, whereas neuroticism and openness are positively associated with this feeling. However, no significant relationship was observed between animosity and agreeableness. In turn, consumer animosity was found to influence product avoidance, and this association became stronger in the case of consumers that have higher levels of power distance, uncertainty avoidance, collectivism, and masculinity. The study also showed that male and educated consumers are more likely to harbor animosity toward a hostility-evoking country, while age and income had no control effect on animosity. Several implications for theory and practice are derived from the study findings, and directions for future research are provided.
Keywords: Consumer animosity; Cultural orientation; Personality; Product avoidance